INCREASING THE VALUE OF WALNUT SHELL (Canarium ovale. L.) WASTE BECOME AROMATHERAPY BRIQUETTES AND ANTI MOSQUITO ON TERNATE ISLAND - Sundari, Sundari; Nurhasanah, Nurhasanah; Papuangan, Numaya; Mas’ud, Abdu (Journal of Islam and Science, 2019)
The purpose of this activity is to introduce the technology of making briquettes to the women of dasawisma, Tarau Village, on the Ternate Island by utilizing walnut shell waste. Community partnership program is college results implementation of Flagship Research 2018 about biobriquette design from walnut shell waste based research studies the value of heat and variations of the adhesive. Output to be achieved was community can entrepreneurship in alternative energy and anti-mosquito so family welfare can be improved. The results of the community dedication program that have been done are as follows: from the aspect of applying science and technology, the briquette product produced  is very effective for building community independence based on local potential namely the use of walnut shell as a local fuel and mosquito repellent with the equivalent SNI quality of coconut shell briquettes. Variation with addition of lavender leaves, dry clove stalk and nutmeg skin increases the use value of walnut shell briquettes to become one of the aromatherapy briquettes and anti-mosquito ingredients which increased people's preference for walnut shell briquettes. Walnut shell briquettes are popular and have economic potential to be marketed as alternative fuels.